Ultraviolet Imaging Telescope (UVIT) observation of the Galactic globular cluster NGC 7492. Issue 1 (6th January 2021) - Kumar, Ranjan; Pradhan, Ananta C; Mohapatra, Abhisek; Moharana, Ayush; Ojha, Devendra K; Parthasarathy, M; Murthy, Jayant
ABSTRACT: We present detailed photometric observations of the Galactic globular cluster NGC 7492 using the data obtained with two far-ultraviolet (FUV; 1300–1800 Å) and three near-ultraviolet (NUV; 2000–3000 Å) filters of Ultraviolet Imaging Telescope (UVIT) onboard the AstroSat satellite. We confirmed the cluster membership of the extracted sources using Gaia data release 2 ( Gaia DR2) proper motion data. We have used colour–magnitude diagrams (CMDs) using UVIT and GAIA filters to separate out different evolutionary stages of the stars present in the cluster. We have identified a new extreme horizontal branch (EHB) star at the core of the cluster using UV and UV-optical CMDs. The estimated distance modulus of the cluster is 16.95 ± 0.05 obtained by fitting BaSTI isochrones with cluster parameters, [Fe/H] = −1.8 dex and age =12.0 Gyr on the V − I versus V CMD. Interestingly, only the EHB star and blue horizontal branch stars (BHBs) among the UV-bright hot sources are detected in FUV filters of UVIT. We have derived the effective temperature of BHBs using colour–temperature relation and spectral energy distributions (SEDs) of multiband filters, which are in the range from 8000 to 10 500 K. We find a variation of He abundance of BHBs by fitting the BaSTI ZAHB (zero-age horizontal branch). The range in the He abundance of the BHBs corresponding to the best-fitting isochrones is from 0.247 to 0.350. We have estimated various physical parameters of the newly identified EHB star in the cluster using SED fit and post-HB evolutionary tracks. We have studied the radial distribution of all the sources of the cluster detected in UVIT. The sources detected in FUV filters extend beyond the half-light radius (1.15 arcmin) of the cluster, whereas the sources detected in NUV filters extend beyond the tidal radius (9.2 arcmin) of the cluster.